MC = MVPA. Issue 4 (3rd May 2020) - Sacko, Ryan S.
Abstract : This article explores the relationship between motor competence and moderate to vigorous physical activity and suggests that the symbiotic relationship between the two means the promotion of one does not have to come at the sacrifice of the other.